Embedded piezoelectric lead-zirconate-titanate-based dynamic internal normal stress sensor for concrete under impact. (November 2017) - Xu, Bin; Song, Gangbing; Mo, YL
The direct stress measurement is critical for the constitutive law investigation of concrete materials and dynamic behavior study of concrete structures under strong dynamic loadings where the strain-rate effect and the plastic behavior should be considered. In this article, an embedded dynamic internal normal stress sensor for concrete by employing piezoelectric lead-zirconate-titanate (PZT) patch as a sensing element is developed. After being calibrated under sinusoidal loadings with different frequencies, periodical square loadings, and random loadings, the developed dynamic internal normal stress sensor is further calibrated with a unique self-developed free-falling drop hammer with different impact velocities. The sensitivity of the developed normal stress sensor is determined accordingly. Finally, the developed sensors are employed to monitor the dynamic normal stress time history at different locations of concrete cylinder specimens under impacts with different velocities using a large-scale drop hammer test facility. The dynamic increase factors of concrete strength under impact are determined and compared with the values determined by the Comité Euro-International du Béton code. The experimental results indicate that the PZT-based embedded dynamic internal normal stress sensor provides a novel way for the direct dynamic normal stress measurement of concrete specimens under impact loadings.